The effects of temperature, pH and sulphide on the community structure of hyperthermophilic streamers in hot springs of northern Thailand - Diane Purcell (2018)
Hyperthermophilic community diversity was assessed in hot-spring streamers along gradients of temperature, pH and sulphide in northern Thailand. A hierarchical sampling design was employed to obtain biomass for culture-independent estimates of 16S rRNA gene-defined prokaryotic diversity. All springs supported several archaeal and bacterial phylotypes, including novel phylotypes that expand the known phylogenetic diversity of terrestrial hyperthermophiles. Diversity appeared significantly greater than that observed for several other geographic locations. Phylotypes belonging to the Aquificales were ubiquitous, further supporting the hypothesis that these chemolithoautotrophs are key members of all hyperthermophilic communities. The chemoorganotrophic genus Thermus was also represented by phylotypes in all springs. Other bacterial taxa represented by environmental sequences included Bacillus, Thermotoga and various unidentified Alphaproteobacteria and Betaproteobacteria. Archaeal phylotypes included the Crenarchaea Desulfurococcus, Pyrobaculum, plus several unidentified hyperthermophilic lineages. A Methanothermococcus-like Euryarchaeon was also identified, with this genus not previously known from streamer communities. A multivariate approach to the analysis of biotic and abiotic data revealed that diversity patterns were best explained by a combination of temperature and sulphide rather than by any other abiotic variable either individually or in combination. © 2007 Federation of European Microbiological Societies.